Postabortal rehabilitation - aspects of the problem: possibilities of combined oral contraceptives - M B Khamoshina; I S Savelyeva; E A Zorina; M S Tulupova; T N Zulumyan (IP Berlin A.V., 2013)
The article presents modern concepts of pharmacological possibilities to use combined oral contraceptives for prevention of various postabortal complications, rational approaches of their use in female patients in postabortal period. The results of studies on efficacy and safety of combined oral contraceptive containing chlormadinone are provided